PENGARUH TEGANGAN TABUNG (kV) PADA PEMERIKSAAN THORAX TERHADAP KUALITAS CITRA RADIOGRAFI DI BALAI BESAR KESEHATAN PARU MASYARAKAT MAKASSAR - Fitriani, Fitriani; Zelviani, Sri; Sahara, Sahara (JFT: Jurnal Fisika dan Terapannya, 2021)
This study aims to determine the effect of high voltage usage and standards on the quality of radiographic imagery produced on X-ray aircraft. Data retrieval was obtained by conducting testing in the Radiology Installation room of the Makassar Public Lung Health Center by using an X-ray aircraft of thosiba brand type with drx-1824B model unit. The result obtained is the voltage of the tube gives an influence on the quality of radiography imagery where for the use of standard tube voltage provides good radiographic imagery quality results with a graph reading histogram voltage of 50 kV with a distance of 100 cm and a time of 10 mAs with a black background image starting at the position of 16 to 36 and the position of the object is 37 to 79 which is then able to provide information because the edges of the object and background can still be distinguished clearly and for the high voltage used the result is less tub because it can reduce the contrast value of objects and background is indistinguishable, this is seen in the histogram readings voltage of 90 kV and distance of 100 cm and the time of 10 mAs has a gradation of gray color that dominates compared to the black background whose position starts from 10 to 132 which can not provide information on the edge value between the background and the object phantom water because both seem to be fused so that it is indistinguishable and causes an inadequate image contrast Not good enough.